Genetic Variability and Heritability for Growth and Quality Traits in Casuarina under Semi-Arid Region of Punjab - Garg, Rakesh K.; Sra, Manpreet S.; Singh, Avtar (Indian Forester, 2024)
Clonal evaluation experiment of Casuarina junghuhniana was established at Research Farm, Bathinda. At the age of 3Â¼ years, growth parameters and stem parameters axis persistence and straightness were recorded. Phenotypic coefficient of variation, genotypic coefficient of variation, heritability and genetic gains were also observed. Maximum PCV and GCV was recorded in tree volume followed by branch thickness. Heritability was recorded maximum for branch thickness (77.93%) followed by tree height (76.25%) and stem volume (70.45%) tree stem volume (21.99%) and crown spread (21.99%). High significant phenotypic correlation was found for tree stem volume with tree height (0. 0.9400) followed by tree stem volume with diameter (0.9328), and diameter and tree height (0.8821). Path analysis demonstrated the direct and indirect effect of the traits on the performance of tree stem volume. The maximum direct effect was registered for diameter at breast height (0.5942) and the least value for direct effect was recorded for crown spread (-0.1417) while the indirect effect was registered maximum by tree height for diameter at breast height (0.5241) and the lowest indirect effect was registered by diameter for number of branches diameter (-0.1816).